Elderly learners in combined-age learning groups picking up on new professional skills - Tiina Tambaum (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2015)
In the study carried out by using qualitative methods, a research instrument for measuring the applicability of principles recommended for the elderly learning in an age-heterogeneous group was created based on geragogy reference sources. The action research of one group showed that most of the principles of geragogy were applied in the study process, although the respective training course was not specifically designed for the elderly. In this combined-age learning group, elderly learners experienced some problems, and recommendations are proposed to solve them.